Self-Frequency Tracking High-Frequency Class E Resonant Inductive Links For Wireless Power Transfer Application - Md Jamal, Norezmi (UTeM, 2016)
Nowadays, Wireless Power Transfer (WPT), specifically based on Inductive Power Transfer (IPT) technology is widely used in mobile applications such as mobile phone, pacemaker, and other applications. It is capable to transfer an electrical power from a power source (transmitter) to an electronic device (receiver) via an air gap, make it flexible and portable to be used for mobile device charger. Therefore, the IPT charger must be compact and small in size. In order to realize it, the coil size should be reduced. So, the operating frequency of the IPT system must be increased significantly to ensure the strongest magnetic field can be generated for a better power transmission. However, as the frequency increases, the switching losses in resonance power converter circuit increase at the same time. Thus, a Class E resonant power converter circuit that yields low switching loss is proposed and designed to drive inductive links with high frequency at transmitter side. In this research, the used operating frequency is 1MHz. To guarantee the maximum power transfer and improvement in efficiency, some studies and experiments on the type of compensated capacitor connection in IPT system were conducted. The simulation and experimental results showed that the external capacitor in series with the transmitter coil improved the result of the induced voltage. Further investigation on capability of larger inductance of inductive links to receive more power with a secondary series compensated capacitor is also conducted. On top of that, since the power transmission is based on the induced voltage concept of two inductive resonance coupling coils, the frequency of the driver circuit may dynamically drift away from the designed circuit. This is because the reflected load impedance exists in transmitter side. In order to rectify the aforementioned problem, a self-frequency tracking approach with feedback loop, which is Phased Lock Loop is proposed to ensure the frequency of the IPT system is operated at 1MHz stably. The analysis of the IPT system with self-frequency tracking performance is validated through LTspice simulations and experimental works. The results revealed that the proposed self-frequency tracking approach improved the power transfer efficiency as compared to without using frequency tracking. Therefore, the total power transfer efficiency of IPT system for simulated results is equal to 84.3% with frequency tracking and 80.6% of without tracking results, respectively. Otherwise, the experimental result of self-frequency tracking is 85.0% and the efficiency of without tracking is 80.4% at 10 mm of air gap distance. Thus, the power transfer efficiency has increased about 4.6% for experimental results.